Coccidohystrix insolita (Green) (Hemiptera: Pseudococcidae) from Indonesia and its note on the three solanaceous plants - Dewi Sartiami; Warniyadi; Nada Rachmatika; Ruly Anwar; Suroto Adisuseno; Watson, Gillian W. (Penerbit Universiti Kebangsaan Malaysia, 2022)
The presence of eggplant mealybug, Coccidohystrix insolita (Green) (Hemiptera: Pseudococcidae) from Indonesia and it infested host plants have been reported in this paper. It was collected in 2017 on cassava, Manihot utilissima in Central Java; additional samples were collected on Turkey berry, Solanum torvum in East and West Java in 2020, and in Aceh (Sumatra) in 2021. In a rearing experiment, the survivorship of C. insolita on three host plant species, Solanum melongena (eggplant), Solanum lycopersicon (tomato), and Capsicum annuum (chilli) was tested; based on the non-parametric Dunn’s test at a 5% level, the mealybug thrives best on Solanum melongena.